ACUTE ST ELEVATION MYOCARDIAL INFARCTION: AFTERCARE AND SECONDARY PREVENTION. NATIONAL RUSSIAN GUIDELINES - M. G. Bubnova; O. L. Barbarash; A. A. Doletsky; V. B. Krasnitsky; E. V. Lebedev; N. P. Lyamina; A. N. Repin; A. V. Light; G. A. Chumakov; D. M. Aronov; A. A. Abdullaev; T. P. Arutyunov; et al. (Российский кардиологический журнал)
.